2017
DOI: 10.1016/j.yjmcc.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine receptor modification and regulation by intracellular Ca2+ and Mg2+ in healthy and failing human hearts

Abstract: Despite different aetiologies, disrupted RyR2 Ca sensitivity and biochemical modification of the channel are common constituents of failing heart RyR2 and may underlie the pathological disturbances in intracellular Ca signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“… 7 , 37 Recently, lipid bilayer experiments on RyR activity support these findings, with a major role for RyR phosphorylation and thiol oxidation in HF conditions. 21 In line with the study from Fischer et al , 7 no differences in response to CaMKII inhibition were found between myocytes from ischaemic and dilated cardiomyopathy (see Supplementary material online, Figure S12 ). The data complement earlier work on the global assessment of Ca 2+ transients in HF vs. non-HF human myocytes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“… 7 , 37 Recently, lipid bilayer experiments on RyR activity support these findings, with a major role for RyR phosphorylation and thiol oxidation in HF conditions. 21 In line with the study from Fischer et al , 7 no differences in response to CaMKII inhibition were found between myocytes from ischaemic and dilated cardiomyopathy (see Supplementary material online, Figure S12 ). The data complement earlier work on the global assessment of Ca 2+ transients in HF vs. non-HF human myocytes.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, previous studies have only reported on overall RyR activity recorded as sparks in diastole and in lipid bilayer experiments, without distinguishing subpopulations. 7 , 21 , 37 They mostly report an increase in total spark frequency, although Lindner et al 10 reported a decrease in HF. An important difference between the aforementioned study and ours is that we studied cells under voltage-clamp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 This observation was expanded to other forms of cardiac disease, including HF, whereby elevated βAR signaling through PKA resulted in hyperphosphorylated S2808 and dissociation of FKBP12.6. 68, 69 These findings have not been universally observed by other investigators have catalyzed a number of follow-up studies which have introduced debate in the field. 70, 71 Some have argued that reduced Ca 2+ reuptake into the SR led is the predominant mechanism underlying HF 72 or that PLN activity and increased SR Ca 2+ load is involved.…”
Section: Arrhythmias Caused By Heritable Defects In Calcium-handling mentioning
confidence: 97%
“…Interestingly, at this concentration, cardiac RyR2 channels incorporated into planar bilayers respond poorly to systolic concentrations of Ca 2+ ( 22 , 23 ). In the failing heart, RyR2 sensitivity to inhibition by cytosolic Mg 2+ is reduced when compared with healthy controls ( 24 ).…”
Section: Resultsmentioning
confidence: 99%